The dynamics of redistribution, inequality and growth across China’s regions - Lucy Barros (Journal of Policy Modeling, 2024)
China’s experience has triggered debate over a trade-off between aggregate growth and regional equity. We develop a three-region model of China where local government decisions are driven by central government tax transfer instruments. These affect local TFP dynamics and regional inequality. We find regional asymmetry in how transfers are awarded. Transfer policies pursued since the 1994 tax-sharing reform prevented a 15% rise in regional inequality, at an 8% cost to aggregate GDP. Temporarily reducing local government non-tax fees on private firms in poorer regions lowers regional inequality permanently at no aggregate growth cost, as would imposing uniformity in central transfer rules.